1992
DOI: 10.1007/bf00243504
|View full text |Cite
|
Sign up to set email alerts
|

Serum cortisol concentration and testosterone to cortisol ratio in elite prepubescent male gymnasts during training

Abstract: Serum cortisol concentrations and testosterone:cortisol concentration ratios of eight prepubescent elite male gymnasts (mean age 10 years 11 months) and 11 controls (mean age 11 years 1 month) were examined during 5 consecutive training days. During this period, the gymnasts trained 3 h each day with moderate intensity mobility, strength and skill exercises while the controls were relatively sedentary. Blood samples were taken from all the boys in both groups before (1630 hours) and 30 min after (2000 hours) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Although data on hormonal responses to exercise in prepubertal children are limited, the results of the present study are consistent with those of Rich et al (1992b), who examined the acute serum cortisol response for 5 consecutive training days in eight trained male gymnasts and eleven untrained similarly aged controls (mean age 11.1 years). In the latter study, no signi®cant dierences were observed between gymnasts and controls immediately prior to or 30 min after gymnastics training at any time throughout the experimental period (Mon±Fri).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although data on hormonal responses to exercise in prepubertal children are limited, the results of the present study are consistent with those of Rich et al (1992b), who examined the acute serum cortisol response for 5 consecutive training days in eight trained male gymnasts and eleven untrained similarly aged controls (mean age 11.1 years). In the latter study, no signi®cant dierences were observed between gymnasts and controls immediately prior to or 30 min after gymnastics training at any time throughout the experimental period (Mon±Fri).…”
Section: Discussionsupporting
confidence: 89%
“…While few studies have examined the T:C ratio in response to training in children and adolescents, no signi®cant dierences were found in the present study between the highly active male gymnasts and normoactive controls over three dierent phases of gymnastics training, although the T:C ratio decreased from PC to SC training in the gymnasts. Rich et al (1992b) found that the T:C ratio decreased in prepubertal male gymnasts compared with controls from the 1st (Monday) to the 3rd (Wednesday) day of gymnastics training, after which the ratio increased following a day's rest (Friday). However, since large day-to-day¯uctuations were observed within the control group, the authors were unable to establish a direct link between training and a reduction in the T:C ratio.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have demonstrated both an increase in testosterone levels as a response to short-term training (4,11,20,29) and a decrease in testosterone levels as a result of both shortterm (23) and long-term training (10,18). The cases where testosterone levels decreased after training involved prolonged endurance-type exercise (i.e., swimming), except in the study of Rich et al (23), who found a decrease in testosterone after 3 days of gymnastics training. In that study, there was, however, an observed return toward preexercise levels after only 1 day of rest, suggesting that the observed changes may have only been transient.…”
Section: Discussionmentioning
confidence: 97%
“…Carli et al (5) found results that were in agreement with this: after 43 wk of swim training, pubertal athletes had testosterone levels that dropped below pretraining levels. Rich et al (23) also found evidence of lowered testosterone with training after only 3 days of training in young gymnasts. Although they did not examine hormonal factors, Keller and Frohner (13) found that male gymnasts undertaking intensive training had reduced height and skeletal maturity relative to chronological age.…”
mentioning
confidence: 91%
“…There are few data however for athletes in the pre-pubertal period [9][10][11] , while the effects of different forms of exercise on sedentary pre-pubertal and pubertal individuals are conflicting. Specifically, T and .AI mean values have been reported to increase [9][10][11] , remain stable [12][13][14] or decrease 15 , following acute intense exercise or two-month to one-year training.…”
Section: Introductionmentioning
confidence: 99%